2003
DOI: 10.1590/s0074-02762003000100008
|View full text |Cite
|
Sign up to set email alerts
|

A bird's eye survey of central american planorbid molluscs

Abstract: In the course of two trips to Central America (June 1967 and JulyAugust 1976) I had the opportunity of collecting topotypic specimens of Planorbis nicaraguanus Morelet, 1849, anatomically defined in this paper, and of P. yzabalensis Crosse & Fischer, 1879, the identity of the latter with Drepanotrema anatinum (Orbigny, 1835) is confirmed. The following planorbid species were also found: Helisoma trivolvis (Say, 1817) in Nicaragua, Guatemala, Costa Rica and Belize; H. duryi (Wetherby, 1879) in Costa Rica; Biomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 7 publications
(6 reference statements)
0
15
0
Order By: Relevance
“…Biomphalaria edisoni n. sp. resembles B. nicaraguana (Paraense, 2003), but differs from it in the following anatomical characters: presence of vaginal pouch; vas deferens notably narrower; ratio between caudal/cephalic portions of the female duct; ratio between cephalic portion of female duct/penial complex.…”
Section: Discussionmentioning
confidence: 93%
“…Biomphalaria edisoni n. sp. resembles B. nicaraguana (Paraense, 2003), but differs from it in the following anatomical characters: presence of vaginal pouch; vas deferens notably narrower; ratio between caudal/cephalic portions of the female duct; ratio between cephalic portion of female duct/penial complex.…”
Section: Discussionmentioning
confidence: 93%
“…Paraense, 1966; Paraense, 1975a; Paraense, 2003; Rumi, 1991). Character similarity among the species, however, has in fact hampered classification, as the case of B. peregrina, B. orbignyi and B. oligoza found in Argentina whose morphological similarities difficult correct identification (Paraense, 1988; Spatz et al, 2000; Vidigal et al, 2000a; Estrada et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Among the Biomphalaria species in South America, B. peregrina exhibits one of the most widespread distributions—and one involving a great diversity of hydrologic systems—with that species thus far having been recorded from Venezuela to northern Patagonia, Argentina (Paraense, 1966; Paraense, 2003; Paraense, 2004; Rumi, 1991; Spatz et al, 2000; Núñez, Gutiérrez Gregoric & Rumi, 2010; Standley et al, 2011). In the study reported here, the presence of B. peregrina in southern Patagonia is now documented for the first time, that location being the southernmost record for the species—and the genus as well—worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Biomphalaria havanensis has a distribution from southern Sonora to Colima, Western Mexico, central and southern Oaxaca and from Tamaulipas to Yucatan on the East (Naranjo-García, 1983), it is also present in Florida, Louisiana and Texas in the US (Burch, 1989), in Cuba and Jamaica, Central America and Venezuela (Yong et al 1995(Yong et al , 2001, in Guatemala it is recorded from Lake Dueñas, in Belize from a pond at Boston Village, in San Salvador at El Salvador as Biomphalaria obstructa (Paraense, 2003). The species Drepanotrema lucidum is distributed in Mexico (Harry and Hubendick, 1964), Central America (Paraense, 2003), Central America, the Greater Antilles, some Bahama Islands, and many of the lesser Antilles (Harry and Hubendick, 1964); it also inhabits in Brazil (Paraense, 1975;Thiengo et al,2004), Peru (Paredes et al, 1999), Uruguay (Scarabino, 2004) and Argentina (Paraense, 2005;Gutiérrez Gregoric et al, 2006). Drepanotrema kermatoides inhabits Florida, Texas, Mexico, Central America, Venezuela, Peru, Brazil and Lesser Antilles (Burch, 1989) at Brazil from Rio Grande Patzner et al, 1996 do Sul and Matto Grosso (Paraense, 1975), it is also found in Peru (Paredes et al, 1999), Uruguay (Scarabino, 2004) and Argentina (Paraense, 2005;Gutiérrez Gregoric et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Planorbula armigera occurs in New Brunswick, Western to South-Eastern Ontario, West to Saskatchewan, Canada, South Georgia and Louisiana and West to Nebraska in the US (Burch, 1989), this is the second record of the genus in Mexico (Naranjo-García -2004-collected it in north east Mexico at Tamaulipas state). Planorbella (Pierosoma) trivolvis is distributed in Canada, the United States (Alaska, the Atlantic coast and the Mississippi River, Tennessee and Missouri) (Burch, 1989), in Mexico at Veracruz and Central America (Nicaragua at Lake Nicaragua; Guatemala at Lake San Cristóbal; Costa Rica from Coris River) (Paraense, 2003); Paredes et al (1999) have also recorded P. trivolvis from Peru (as Helisoma trivolvis). Pomacea fl agellata is distributed from northern Veracruz, Tabasco, Quintana Roo, Chiapas in Mexico, Central America to Colombia (Naranjo-García and García-Cubas, 1986).…”
Section: Discussionmentioning
confidence: 99%